Pemantauan Kinerja Sistem Manajemen Kesehatan Keselamatan Kerja Lindung Lingkungan berdasarkan ISO 45001, 14001 dan 9001 di KSO CESL - Sri Suhardono; Bambang Pramudya Noorachmat; Andes Ismayana (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Monitoring Performance of Occupational Health Safety and Environmental Protection Management System (OHSEMS) Based on ISO 45001, 14001 and 9001 is a methodological approach to managing interaction for implementation policies, processes, and regulations. Risk identification modeling used to ensure that activities can run properly in accordance with regulations and standards which are part of the performance management system measurement. Risk control modeling as a verification tool for OHSE events in drilling activities as much as 90, producing 325. Stakeholder regulations as many as 27 with total expectations 108 out of a total of 28 revisions with a total expectation of 225 in standard regulatory database modeling. OHSEMS improvement uses data on OHSE events from 2013 to June 2018. Drilling activities have 16 events with a number of standard regulations 14 and the number of suggestions for improvement 23, the number of recommended suggestion as many as 16. Production activities there are 25 occurrences of the number of standard regulations 16 with suggestions improvements 42 and recommendations for improvements was 25. In the OHSEMS improvement in drilling activities based on OHSE events is to socialize drilling work procedures. In production activities to reduce the occurrence of oil spills that can cause environmental impacts, make improvements to facilities as well as emergency response prevention training can be done to control events caused by human factors and production equipment